The effect of dangerous goods transporters on hazard perception and evacuation behavior – A virtual reality experiment on tunnel emergencies. (November 2015) - Kinateder, Max; Gromer, Daniel; Gast, Philipp; Buld, Susanne; Müller, Mathias; Jost, Michael; Nehfischer, Markus; Mühlberger, Andreas; Pauli, Paul
Abstract: Introduction: Evacuation from tunnel fire emergencies may become problematic if tunnel occupants do not engage quickly enough into evacuation. Dangerous goods transporters increase the risks tunnel occupants are exposed to. The aim of the present study is to investigate the effect of an increased risk during a simulated tunnel emergency on participants' subjective hazard perception and evacuation behavior. Methods: Using a five sided CAVE system, two experimental groups were immersed into a virtual road tunnel fire emergency. In the dangerous goods condition a burning gasoline transporter was visible. In the control condition a burning heavy goods vehicle was visible. Hazard perception, pre-movement time, movement time and exit choices were analyzed. Results: In the dangerous goods condition the situation was rated significantly more dangerous than in the control condition. In both conditions participants showed appropriate behavioral reactions and either moved to an emergency exit or to an emergency phone. Discussion: In combination with the high threat ratings the results indicate good situation awareness of the participants, and that emergency signage in the given visibility conditions was effective in guiding participants towards an exit or to an emergency phone. Highlights: Study on the effect of dangerous goods on hazard perception and evacuation behavior. Virtual reality simulation of a tunnel emergency with and without a dangerous goods transporter. Seeing a dangerous goods transporter increased the perceived threat during the tunnel fire. Most but not all participants reacted appropriately to the fire emergency.